Solar cell, method of manufacturing the same, and photovoltaic module
Patent Information
- Application Number
- CN202610798551.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有的铜浆料在太阳能电池金属化的过程中,铜粉极易发生氧化,无法形成致密的烧结层,导致制备的栅线存在孔隙率高、导电率低等问题,使得栅线具有高的线电阻率,影响太阳能电池和光伏组件的效率,而且,采用其制备的光伏组件在运行过程中还会出现水汽侵入导致的氧化失效,导致光伏组件可靠性差
[0028] The solar cell of this invention employs copper grid lines, selectively coating the surface of the copper grid lines with a silicone oil curing layer of a specific thickness. During the fabrication of the copper grid lines, the copper particles in the copper paste are copper powder coated with a reducing organic layer. Simultaneously, a flexible composite film with a specific structure or silicone oil containing a curing agent is used, along with a hot-pressing curing process. Through this synergistic effect, the copper paste effectively inhibits the oxidation of copper particles during the entire metallization process of the solar cell. This ensures that the copper powder in the copper paste is almost entirely pure copper powder, resulting in a low porosity and high density in the final copper grid lines. This effectively improves their conductivity, thereby achieving a line resistivity of less than or equal to 8 × 10⁻⁶. -7 With a low linear resistivity of Ω·m, it can effectively improve the efficiency of solar cells and photovoltaic modules, while also reducing the permeation paths of water vapor and oxygen to a certain extent, thus providing a certain degree of water vapor barrier and improving the reliability of photovoltaic modules. Furthermore, the excellent chemical stability, high temperature resistance, and strong hydrophobicity of the silicone oil curing layer can be utilized to significantly improve the oxidation resistance and water vapor barrier properties of the copper grid lines, further enhancing the reliability of photovoltaic modules.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic cell technology, and in particular to solar cells, their preparation methods, and photovoltaic modules. Background Technology
[0002] To reduce costs, copper paste is primarily used instead of silver paste to prepare the grid lines of solar cells. However, during the metallization process of solar cells, the copper powder in existing copper paste is prone to oxidation, making it impossible to form a dense sintered layer. This results in grid lines with high porosity and low conductivity, leading to high line resistivity and affecting the efficiency of solar cells and photovoltaic modules. Furthermore, photovoltaic modules made with this paste are susceptible to oxidation failure due to moisture intrusion during operation, resulting in poor reliability. Summary of the Invention
[0003] Therefore, it is necessary to address the aforementioned problems by providing a solar cell, its fabrication method, and a photovoltaic module. This solar cell, due to the low linear resistivity and moisture barrier properties of its copper grid lines, can effectively improve both the efficiency and reliability of the solar cell and the photovoltaic module.
[0004] A solar cell includes a silicon wafer and grid lines disposed on at least the surface of the silicon wafer. The grid lines are copper grid lines, and the surface of the copper grid lines is coated with a silicone oil curing layer with a thickness of 0 nm-500 nm. The line resistivity of the copper grid lines is less than or equal to 8 × 10⁻⁶. -7 Ω·m.
[0005] In one embodiment, the copper grid line includes a first region for solder ribbon connection and a second region other than the first region, wherein the thickness of the silicone oil curing layer covering the first region is 0nm-100nm, and the thickness of the silicone oil curing layer covering the second region is 100nm-500nm.
[0006] In one embodiment, the line resistivity of the copper gate wire is 8 × 10⁻⁶. -7 Ω·m⁻¹×10 -8 Ω·m.
[0007] In one embodiment, the surface of the copper grid line is further coated with an antioxidant layer, and the silicone oil curing layer is located between the antioxidant layer and the copper grid line;
[0008] And / or, the silicone oil curing layer contains conductive particles, and the mass fraction of the conductive particles in the silicone oil curing layer is 5%-50%.
[0009] In one embodiment, the copper grid line includes a first region for solder ribbon connection and a second region other than the first region, wherein the thickness of the antioxidant layer covering the first region is 1nm-50nm and the thickness of the antioxidant layer covering the second region is 20nm-200nm.
[0010] And / or, the material of the antioxidant layer is selected from silicon nitride and / or magnesium fluoride.
[0011] A method for preparing a solar cell includes the following steps:
[0012] A copper paste is provided, wherein the copper particles in the copper paste are copper powder with a reducing organic layer on the surface;
[0013] The copper paste is placed on at least one surface of a silicon wafer and dried to form a paste layer. A flexible composite film is then covered on the surface of the paste layer and a copper grid line is formed by hot pressing and curing. The flexible composite film is removed to obtain a solar cell. The flexible composite film includes a flexible substrate and a silicone oil curing layer covering the surface of the flexible substrate, and the hot pressing and curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer.
[0014] Alternatively, a copper paste may be provided, wherein the copper particles in the copper paste are copper powder with a reducing organic layer on the surface;
[0015] The copper paste is placed on at least one surface of a silicon wafer to form a paste layer. Then, silicone oil containing a curing agent is placed on the surface of the paste layer. After drying and hot pressing curing, copper grid lines are formed to obtain a solar cell. The hot pressing curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer.
[0016] In one embodiment, the copper paste contains 80%-90% copper particles by mass.
[0017] And / or, the thickness of the reducing organic layer is 1 nm-50 nm;
[0018] And / or, the material of the reducing organic layer is selected from thiols and / or isopropanol;
[0019] And / or, the hot-press curing temperature is 200℃-300℃, the hot-press curing pressure is 10Pa-10KPa, and the hot-press curing time is 1s-30s;
[0020] And / or, the mass fraction of the silicone oil containing the curing agent on the silicon wafer with the slurry layer is 0.01%-1%;
[0021] And / or, the silicone oil containing the curing agent also contains conductive particles, wherein the mass fraction of the conductive particles in the silicone oil containing the curing agent is 5%-50%.
[0022] In one embodiment, the thickness of the flexible composite film is 20μm-1000μm;
[0023] And / or, the thickness of the silicone oil curing layer in the flexible composite film is 0.1 μm-10 μm;
[0024] And / or, the material of the flexible substrate is selected from at least one of polyimide, polytetrafluoroethylene, and glass fiber.
[0025] In one embodiment, the method for fabricating the solar cell further includes: preparing an antioxidant layer on the surface of a silicon wafer with the copper grid lines;
[0026] Alternatively, the method for preparing the solar cell may further include: preparing an antioxidant layer on the surface of a silicon wafer with the copper grid lines, and / or performing a light injection treatment on the silicon wafer with the copper grid lines in a low-oxygen atmosphere, wherein the oxygen content in the low-oxygen atmosphere is 100ppm-500ppm.
[0027] A photovoltaic module, the photovoltaic module comprising the aforementioned solar cell.
[0028] The solar cell of this invention employs copper grid lines, selectively coating the surface of the copper grid lines with a silicone oil curing layer of a specific thickness. During the fabrication of the copper grid lines, the copper particles in the copper paste are copper powder coated with a reducing organic layer. Simultaneously, a flexible composite film with a specific structure or silicone oil containing a curing agent is used, along with a hot-pressing curing process. Through this synergistic effect, the copper paste effectively inhibits the oxidation of copper particles during the entire metallization process of the solar cell. This ensures that the copper powder in the copper paste is almost entirely pure copper powder, resulting in a low porosity and high density in the final copper grid lines. This effectively improves their conductivity, thereby achieving a line resistivity of less than or equal to 8 × 10⁻⁶. -7 With a low linear resistivity of Ω·m, it can effectively improve the efficiency of solar cells and photovoltaic modules, while also reducing the permeation paths of water vapor and oxygen to a certain extent, thus providing a certain degree of water vapor barrier and improving the reliability of photovoltaic modules. Furthermore, the excellent chemical stability, high temperature resistance, and strong hydrophobicity of the silicone oil curing layer can be utilized to significantly improve the oxidation resistance and water vapor barrier properties of the copper grid lines, further enhancing the reliability of photovoltaic modules.
[0029] Therefore, the solar cell of the present invention, due to the low linear resistivity and water vapor barrier properties of the copper grid lines, can effectively improve the efficiency and reliability of the photovoltaic module. Detailed Implementation
[0030] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional range of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0032] The solar cell provided by this invention includes a silicon wafer and grid lines disposed on at least the surface of the silicon wafer. The grid lines are copper grid lines, and the surface of the copper grid lines is coated with a silicone oil curing layer with a thickness of 0 nm-500 nm. The line resistivity of the copper grid lines is less than or equal to 8 × 10⁻⁶. -7 Ω·m.
[0033] It is understood that in the solar cell of the present invention, the copper grid lines have two structures. The first structure is when the thickness of the silicone oil curing layer is 0 nm, that is, the surface of the copper grid lines is not covered with a silicone oil curing layer, and the line resistivity of the copper grid lines is less than or equal to 8 × 10⁻⁶. -7 Ω·m; Second structure: When the thickness of the silicone oil curing layer is greater than 0 and less than or equal to 500 nm, that is, the surface of the copper grid line is covered with a silicone oil curing layer, and the line resistivity of the copper grid line is less than or equal to 8 × 10⁻⁶. -7 Ω·m, the second structure is preferred in this invention. With this configuration, since the copper grid surface is coated with a silicone oil curing layer as a protective layer, the requirements for the copper grid's moisture barrier performance and oxidation resistance can be reduced, thereby lowering the requirements for the copper grid manufacturing process.
[0034] Specifically, when the thickness of the silicone oil curing layer covering the surface of the copper grid line is 0 nm, the copper particles in the copper paste used in the fabrication process are copper powder with a reducing organic coating. Simultaneously, a flexible composite film with a specific structure or silicone oil containing a curing agent is employed, along with a hot-press curing process. Under this synergistic effect, the copper paste effectively inhibits the oxidation of copper particles during the entire solar cell metallization process. This ensures that the copper powder in the copper paste is almost entirely pure copper powder, resulting in low porosity and high density in the final copper grid line. This effectively improves its conductivity, thereby making the line resistivity of the copper grid line less than or equal to 8 × 10⁻⁶. -7 With a resistivity of Ω·m, it has a low linear resistivity, which can effectively improve the efficiency of solar cells and photovoltaic modules. At the same time, it can also reduce the permeation path of water vapor and oxygen to a certain extent, and has a certain water vapor barrier, which is beneficial to improving the reliability of photovoltaic modules.
[0035] When the thickness of the silicone oil curing layer covering the surface of the copper grid line is greater than 0 mm, the silicone oil curing layer serves as a protective layer for the copper grid line. Utilizing the excellent chemical stability, high temperature resistance, and strong hydrophobicity of the silicone oil curing layer, it can significantly improve the oxidation resistance and water vapor barrier properties of the copper grid line, further enhancing the reliability of the photovoltaic module.
[0036] It is understood that the solar cells of the present invention, regardless of whether the thickness of the silicone oil curing layer on the surface of the copper grid lines is 0 nm or greater than 0 nm, all have low linear resistivity and a certain degree of water vapor barrier properties, which can effectively improve the efficiency and reliability of the photovoltaic module. In particular, when the thickness of the silicone oil curing layer on the surface of the copper grid lines is greater than 0 nm, the water vapor barrier properties of the copper grid lines are better, which can further improve the reliability of the photovoltaic module.
[0037] Therefore, the solar cell of the present invention, due to the low linear resistivity and water vapor barrier properties of the copper grid lines, can effectively improve the efficiency and reliability of the photovoltaic module.
[0038] It should be noted that when the surface of the copper grid wire is coated with a silicone oil curing layer, the surface of the copper grid wire can be partially or completely covered by the silicone oil curing layer. Furthermore, in this invention, the silicone oil curing layer is formed by curing silicone oil, preferably dimethyl silicone oil; that is, the silicone oil curing layer is preferably a dimethyl silicone oil curing layer. Compared to ordinary polymer layers, this silicone oil curing layer is not easily corroded even when in contact with acetic acid, ensuring the durability of the water vapor barrier properties of the copper grid wire, enabling it to operate stably for a long time and further improving the reliability of the photovoltaic module.
[0039] Optionally, the line resistivity of the copper grid line is 8 × 10⁻⁶. -7 Ω·m⁻¹×10-8 Ω·m.
[0040] Considering that the thickness of the silicone oil curing layer affects the conductivity of the copper grid lines, especially the conductivity of the copper grid line area connected by solder ribbon, in this invention, the copper grid lines include a first area for solder ribbon connection and a second area other than the first area. The thickness of the silicone oil curing layer covering the first area is 0nm-100nm, and the thickness of the silicone oil curing layer covering the second area is 100nm-500nm.
[0041] It is understood that the first area on the surface of the copper grid line used for solder strip connection may be coated with a silicone oil curing layer or not. When the first area is coated with a silicone oil curing layer, its thickness is thinner than that of the second area. This design allows the first area of the copper grid line to maintain good conductivity (i.e., low line resistivity) while possessing oxidation resistance and moisture barrier properties. Therefore, in this invention, by controlling the thickness of the silicone oil curing layer in the first and second areas, the oxidation resistance and moisture barrier properties of the copper grid line can be improved without affecting its conductivity, further enhancing the reliability of the photovoltaic module.
[0042] Optionally, the silicone oil curing layer contains conductive particles, and the mass fraction of the conductive particles in the silicone oil curing layer is 5%-50%. It can be understood that in this case, the silicone oil curing layer is formed by the curing of conductive particles and silicone oil. The conductive particles dispersed in the silicone oil curing layer can form conductive pathways, which helps to improve the overall conductivity of the silicone oil curing layer. This, in turn, enables the copper grid wire to have good oxidation resistance and moisture barrier properties while further reducing the line resistivity of the copper grid wire.
[0043] Furthermore, the conductive particles are selected from at least one of silver powder, tin-zinc alloy (melting point 210℃), carbon black, carbon nanotubes (CNT), and graphene.
[0044] To further improve the oxidation resistance and moisture barrier properties of the copper grid lines and better enhance the reliability of photovoltaic modules, in this invention, the surface of the copper grid lines is also coated with an anti-oxidation layer, and the silicone oil curing layer is located between the anti-oxidation layer and the copper grid lines.
[0045] Considering that the thickness of the anti-oxidation layer affects the conductivity of the copper grid wire, in this invention, the copper grid wire includes a first region for solder ribbon connection and a second region other than the first region. The thickness of the anti-oxidation layer covering the first region is 1nm-50nm, and the thickness of the anti-oxidation layer covering the second region is 20nm-200nm. With this configuration, by controlling the thickness of the anti-oxidation layer in the first and second regions, it is possible to better ensure that the oxidation resistance and moisture barrier properties of the copper grid wire are further improved without affecting its conductivity, thereby improving the reliability of the photovoltaic module.
[0046] Furthermore, the material of the antioxidant layer is selected from silicon nitride and / or magnesium fluoride.
[0047] Meanwhile, the present invention also provides a method for preparing a solar cell, comprising the following steps:
[0048] S1, providing copper paste, wherein the copper particles in the copper paste are copper powder with a reducing organic layer on the surface;
[0049] S2, the copper paste is placed on at least one surface of a silicon wafer, dried to form a paste layer, and then a flexible composite film is covered on the surface of the paste layer. Copper grid lines are formed by hot-pressing and curing. The flexible composite film is removed to obtain a solar cell. The flexible composite film includes a flexible substrate and a silicone oil curing layer covering the surface of the flexible substrate, and the hot-pressing curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer. Alternatively, the copper paste is placed on at least one surface of a silicon wafer to form a paste layer, and then silicone oil containing a curing agent is placed on the surface of the paste layer. The mixture is dried and hot-pressed to form copper grid lines to obtain a solar cell. The hot-pressing curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer.
[0050] In this invention, the copper particles in the copper paste are copper powder coated with a reducing organic layer. This gives the copper paste excellent oxidation resistance, effectively preventing oxygen from contacting the copper powder and reducing its oxidation. Furthermore, during curing, because the hot-pressing curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer, the reducing organic layer decomposes and releases reducing gases. These reducing gases can reduce the oxidized copper powder. Simultaneously, by covering the surface of the paste layer with a flexible composite film or coating it with silicone oil containing a curing agent, contact between oxygen and the copper paste can be further isolated. During curing, the reducing gases released from the decomposition of the reducing organic layer are sealed around the copper paste, effectively inhibiting the oxidation of the copper particles. This ensures that the copper powder in the copper paste is pure copper powder throughout the entire solar cell metallization process, resulting in copper grid lines with low porosity and high density. Moreover, when silicone oil containing a curing agent is used, the silicone oil containing the curing agent will form a silicone oil curing layer on the surface of the copper grid line as a protective layer, which significantly improves the oxidation resistance and moisture barrier properties of the copper grid line.
[0051] Furthermore, the hot-press curing process, compared to the traditional low-temperature sintering process, utilizes the good thermal conductivity of copper to conduct heat through thermal contact. On the one hand, it can achieve rapid sintering of copper paste, reducing the risk of copper powder oxidation during curing. On the other hand, it can achieve compaction between the components in the copper paste, expel gases (such as unreacted reducing gases) from the copper paste, further reduce the porosity of the copper grid lines, and further improve the density of the copper grid lines.
[0052] Therefore, in the solar cell fabrication method of the present invention, the copper particles in the copper paste are copper powder with a reducing organic layer coated on the surface. Simultaneously, a flexible composite film with a specific structure or silicone oil containing a curing agent is used, along with a hot-pressing curing process. Under this synergistic effect, the oxidation of the copper particles can be effectively suppressed, ensuring that the copper powder in the copper paste is almost entirely pure copper powder throughout the entire solar cell metallization process. This results in the final copper grid lines having low porosity and high density, thereby significantly reducing the linear resistivity of the copper grid lines to less than or equal to 8 × 10⁻⁶. -7 With a resistivity of Ω·m, it exhibits low linear resistivity, improving the efficiency of solar cells and photovoltaic modules while reducing the permeation paths of water vapor and oxygen to a certain extent, thus providing a certain degree of water vapor barrier and enhancing the reliability of photovoltaic modules. Furthermore, when silicone oil containing a curing agent is used, a silicone oil curing layer forms on the surface of the copper grid lines as a protective layer, significantly improving the oxidation resistance and water vapor barrier properties of the copper grid lines, effectively enhancing the reliability of photovoltaic modules.
[0053] In addition, the hot-press curing process used in this invention has a very short curing time, so the flexible composite film or silicone oil curing layer will not be damaged during the entire curing process, thus reducing the risk of oxidation and having little impact on the performance of the silicon wafer.
[0054] It is understood that, in this invention, based on step S1, a flexible composite film or silicone oil containing a curing agent can be selectively coated on the surface of the slurry layer according to actual needs to obtain the corresponding copper grid structure. Specifically, when a flexible composite film is coated on the surface of the slurry layer, the surface of the final copper grid is not covered with a silicone oil curing layer, that is, the thickness of the silicone oil curing layer is 0 nm, corresponding to the first type of copper grid structure described above; when silicone oil containing a curing agent is coated on the surface of the slurry layer, the surface of the final copper grid is covered with a silicone oil curing layer, that is, the thickness of the silicone oil curing layer is greater than 0 nm, corresponding to the second type of copper grid structure described above.
[0055] In step S1, the copper paste includes copper particles, a curing agent, and an organic solvent, wherein the mass fraction of copper particles in the copper paste is 80%-90%; this setting enables the copper paste to have good electrical conductivity while also having good fluidity, making it easy to print.
[0056] Optionally, the thickness of the reducing organic layer is 1nm-50nm. With this setting, the amount of reducing gas released by the thermal decomposition of the reducing organic layer during the curing process can be controlled by adjusting the thickness of the reducing organic layer, so that the reducing gas can fully react with the copper oxide powder and be reduced to copper powder, while avoiding excessive reducing gas from affecting the density of the copper grid lines.
[0057] Optionally, the material of the reducing organic layer is selected from thiol compounds and / or isopropanol / or copper formate / or ethanol or a mixture of thiol compounds and copper formate, preferably thiol compounds, and more preferably octadecyl mercaptan. It is understood that thiol compound molecules form Cu-S chemical bonds with the copper surface through their thiol groups, enhancing the bonding strength between the reducing organic layer and copper. Furthermore, during the curing process, they decompose into reducing gases, which can reduce copper oxide powder to copper powder.
[0058] In this invention, the copper particles in the copper paste (i.e., copper powder with a reducing organic layer on the surface) can be purchased from the market or prepared by conventional methods. Specifically, in one embodiment, the preparation method of copper powder with a reducing organic layer on the surface includes the following steps: cleaning the original copper powder in an acid solution, then forming a protective film on the surface of the original copper powder using a copper passivating agent; finally, reacting the original copper powder in a reducing organic layer precursor solution to obtain copper powder with a reducing organic layer on the surface.
[0059] The copper passivating agent is preferably benzotriazole; the reducing organic layer precursor solution is preferably a thiol compound solution, and more preferably an isopropanol solution of octadecyl mercaptan; the reaction temperature is 10℃-35℃.
[0060] When the precursor solution of the reducing organic layer is a thiol compound solution, a reducing agent can be added to the small molecule alcohol solution of the thiol compound to promote the reaction of the thiol compound with the copper surface, thereby enhancing the bonding strength between copper and the reducing organic layer. Sodium borohydride is preferred as the reducing agent.
[0061] In step S2, when a flexible composite film is covered on the surface of the slurry layer, the flexibility of the flexible composite film can effectively cover the surface of the slurry layer, preventing the slurry layer from contacting oxygen. In order to better prevent the oxidation of copper paste while reducing the influence of the flexible composite film on the heat conduction rate during the curing process, the thickness of the flexible composite film in this invention is 20μm-1000μm. This setting allows for control of the thickness of the flexible composite film, enabling it to have good flexibility without affecting the heat conduction rate, which is beneficial for achieving faster curing of the copper grid lines.
[0062] Optionally, the thickness of the silicone oil curing layer in the flexible composite film is 0.1μm-10μm. With this setting, by adjusting the thickness of the silicone oil curing layer, the high temperature resistance and chemical stability of the silicone oil curing layer can be utilized to effectively prevent the flexible composite film from reacting with the components in the copper paste. At the same time, it can better reduce the risk of copper powder oxidation, and can avoid scratching the copper grid lines and silicon wafers, thus ensuring the integrity of the entire copper grid lines and silicon wafers.
[0063] Furthermore, the material of the flexible substrate is selected from at least one of polyimide, polytetrafluoroethylene, and glass fiber, preferably polyimide.
[0064] In one embodiment, the preparation method of the flexible composite film is as follows: a flexible substrate is provided, a silicone oil containing a curing agent is coated on the surface of the flexible substrate, and then dried to form a flexible substrate with a silicone oil curing layer on the surface, thereby obtaining a flexible composite film. The silicone oil containing the curing agent is preferably dimethyl silicone oil containing the curing agent, and the curing agent is selected from at least one of benzoyl peroxide (BPO), methyl ethyl ketone peroxide, tetraisopropyl titanate, and dibutyltin dilaurate.
[0065] In step S2, the copper paste is placed on at least one surface of the silicon wafer to form a paste layer, and then dried to form a paste layer.
[0066] In one embodiment, the copper paste is printed onto at least one surface of the silicon wafer using screen printing or laser transfer.
[0067] In the step of placing silicone oil containing curing agent on the surface of the slurry layer, the mass fraction of silicone oil containing curing agent on the silicon wafer with slurry layer is 0.01%-1%; this setting can control the thickness of the silicone oil curing layer covering the surface of the copper grid lines.
[0068] Optionally, the silicone oil containing a curing agent further contains conductive particles, wherein the conductive particles constitute 5%-50% of the silicone oil containing the curing agent by mass, and the conductive particles are selected from at least one of silver powder, tin-zinc alloy (melting point 210℃), carbon black, carbon nanotubes (CNTs), and graphene. It can be understood that, in this case, the silicone oil containing the curing agent is obtained by mixing the curing agent, silicone oil, and conductive particles.
[0069] In one embodiment, the silicone oil containing the curing agent has a silicone oil mass fraction of 49.5%-99%.
[0070] In one embodiment, the silicone oil containing a curing agent is preferably a dimethyl silicone oil containing a curing agent, wherein the curing agent is selected from at least one of benzoyl peroxide (BPO), dichlorobenzoyl peroxide (DCBP), dicumyl peroxide (DCP), methyl ethyl ketone peroxide, tetraisopropyl titanate, dibutyltin dilaurate, tetraethoxysilane (TEOS), and methyltrimethoxysilane (MTMS).
[0071] It is understood that in step S2, whether it is the step of covering the surface of the slurry layer with a flexible composite film, curing it by hot pressing to form copper grid lines, and then removing the flexible composite film, or the step of placing silicone oil containing curing agent on the surface of the slurry layer, drying it, and curing it by hot pressing to form copper grid lines, the hot pressing curing conditions are the same. Specifically, the hot pressing curing temperature is 200℃-300℃, preferably 275℃; the hot pressing curing pressure is 10Pa-10KPa, preferably 20Pa; and the hot pressing curing time is 1s-30s, preferably 3s. This setting can better achieve rapid sintering of the copper slurry, reduce the risk of copper powder oxidation during curing, and better achieve compaction between the components in the copper slurry, further reducing the porosity of the copper grid lines and increasing their density.
[0072] In this invention, the method for preparing the solar cell further includes: preparing an anti-oxidation layer on the surface of a silicon wafer with the copper grid lines, and / or performing a light injection treatment on the silicon wafer with the copper grid lines under a low-oxygen atmosphere, wherein the oxygen content in the low-oxygen atmosphere is 100ppm-500ppm.
[0073] It is understood that the method for preparing the solar cell in this invention further includes the following three steps:
[0074] The first method involves preparing an anti-oxidation layer on the surface of a silicon wafer with the copper grid lines. This configuration improves the oxidation resistance and moisture barrier properties of the copper grid lines, thereby enhancing the reliability of the photovoltaic module.
[0075] The second method involves performing light injection treatment on the silicon wafer with the copper grid lines in a low-oxygen atmosphere, wherein the oxygen content in the low-oxygen atmosphere is 100ppm-500ppm. This setting enables light injection in a low-oxygen atmosphere, improving the efficiency of the solar cell while effectively preventing the oxidation of the copper grid lines.
[0076] The third method involves preparing an antioxidant layer on the surface of a silicon wafer with copper grid lines and performing photoinjection treatment on the silicon wafer with copper grid lines in a low-oxygen atmosphere, wherein the oxygen content in the low-oxygen atmosphere is 100ppm-500ppm; preferably, an antioxidant layer is first prepared on the surface of the silicon wafer with copper grid lines, and then the silicon wafer with copper grid lines is placed in a low-oxygen atmosphere for photoinjection treatment, wherein the oxygen content in the low-oxygen atmosphere is 100ppm-500ppm; this setup can improve the oxidation resistance and moisture barrier properties of the copper grid lines, thereby improving the reliability of the photovoltaic module and the efficiency of the solar cell and photovoltaic module.
[0077] The third method is preferred in this invention.
[0078] In one embodiment, the material of the antioxidant layer is selected from silicon nitride and / or magnesium fluoride.
[0079] When the material of the antioxidant layer is selected from silicon nitride, the plate PECVD method is used to prepare the antioxidant layer on the surface of the silicon wafer with the copper grid lines using SiH4 and NH3.
[0080] When the material of the antioxidant layer is selected from magnesium fluoride, the antioxidant layer is prepared on the surface of the silicon wafer with the copper grid lines by thermal evaporation.
[0081] It should be noted that due to the special structure of the gate lines (such as spherical shape), the thickness of the silicone oil curing layer differs in the first and second regions of the gate lines. Similarly, when preparing the antioxidant layer, its thickness differs in the first and second regions of the gate lines.
[0082] In one embodiment, the light injection temperature is 150°C-250°C, preferably 200°C, the light injection intensity is 30 mins-60 mins, and the light injection time is 1 min-1.5 min.
[0083] In one embodiment, the low-oxygen atmosphere is preferably a nitrogen atmosphere and / or an inert gas atmosphere.
[0084] It should be noted that in this invention, the silicon wafer actually refers to the solar cell on which the grid lines are to be fabricated. Furthermore, this invention does not specifically limit the type of solar cell; it can be a heterojunction solar cell, TOPCon, PERC cell, etc., preferably a heterojunction solar cell. It can be understood that when the solar cell is a heterojunction solar cell, the silicon wafer refers to the heterojunction solar cell on which the grid lines are to be fabricated, and this silicon wafer includes a texturized silicon substrate, on both the front and back sides of which an intrinsic amorphous silicon layer, a doped layer, and a TCO layer are sequentially stacked, and the grid lines are provided on the TCO layer.
[0085] In addition, the present invention also provides a photovoltaic module, the photovoltaic module including the solar cell described above.
[0086] The following specific embodiments will further illustrate the solar cell, its preparation method, and photovoltaic module. However, those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0087] It should be noted that the silicon wafers mentioned in the embodiments and comparative examples of this invention refer to heterojunction solar cells on which the grid lines are to be fabricated.
[0088] Example 1
[0089] A copper paste was prepared by coating copper powder with an octadecyl mercaptan layer, 2-ethyl-4-methylimidazolium curing agent, and diethylene glycol butyl ether. The copper paste contained 85% copper powder by mass, 0.5% 2-ethyl-4-methylimidazolium curing agent by mass, and the thickness of the octadecyl mercaptan layer was 25 nm.
[0090] The aforementioned copper paste was screen-printed onto both sides of a silicon wafer, dried to form a paste layer, and then a 50 μm thick flexible composite film was coated onto the surface of the paste layer. Copper grid lines were formed by hot-pressing and curing. The flexible composite film was then removed. The hot-pressing curing temperature was 275°C, the hot-pressing curing pressure was 1000 Pa, and the hot-pressing curing time was 3 s. A silicon nitride layer was then prepared on the surface of the silicon wafer with the copper grid lines using PECVD. The wafer was then subjected to photoinjection in a low-oxygen atmosphere. The photoinjection temperature was 220°C, and the photoinjection intensity was 60 sun. A heterojunction solar cell is obtained by using a light injection time of 90s and an oxygen content of 200ppm in a low-oxygen atmosphere. The flexible composite film includes a polyimide substrate and a dimethyl silicone oil curing layer covering the surface of the polyimide substrate. The thickness of the dimethyl silicone oil curing layer is 5μm. The copper grid line includes a first region for solder ribbon connection and a second region other than the first region. The thickness of the silicon nitride layer covering the first region is 25nm, and the thickness of the silicon nitride layer covering the second region is 100nm.
[0091] Example 2
[0092] A copper paste was prepared by coating copper powder with a dodecyl mercaptan layer, 2-ethyl-4-methylimidazolium curing agent, and diethylene glycol butyl ether. The copper paste contained 80% copper powder by mass, 0.3% 2-ethyl-4-methylimidazolium curing agent by mass, and 25 nm thick dodecyl mercaptan layer.
[0093] The aforementioned copper paste was screen-printed onto both sides of a silicon wafer, dried to form a paste layer, and then a 50 μm thick flexible composite film was coated onto the surface of the paste layer. Copper grid lines were formed by hot-pressing and curing. The flexible composite film was then removed. The hot-pressing curing temperature was 200℃, the hot-pressing curing pressure was 90 Pa, and the hot-pressing curing time was 30 s. A silicon nitride layer was then prepared on the surface of the silicon wafer with the copper grid lines using PECVD. The wafer was then subjected to photoinjection treatment in a low-oxygen atmosphere. The photoinjection temperature was 220℃, and the photoinjection intensity was 60 suns. A heterojunction solar cell was obtained by using a light injection time of 90s and an oxygen content of 100ppm in a low-oxygen atmosphere. The flexible composite film includes a glass fiber substrate and a dimethyl silicone oil curing layer covering the surface of the glass fiber substrate. The thickness of the dimethyl silicone oil curing layer is 0.5μm. The copper grid line includes a first region for solder ribbon connection and a second region other than the first region. The thickness of the silicon nitride layer covering the first region is 2nm, and the thickness of the silicon nitride layer covering the second region is 25nm.
[0094] Example 3
[0095] A copper paste was prepared by coating copper powder with an octadecyl mercaptan layer, 2-ethyl-4-methylimidazolium curing agent, and diethylene glycol butyl ether. The copper paste contained 90% copper powder by mass, 1% 2-ethyl-4-methylimidazolium curing agent by mass, and the thickness of the octadecyl mercaptan layer was 50 nm.
[0096] The aforementioned copper paste is screen-printed onto both sides of a silicon wafer, dried to form a paste layer, and then a flexible composite film with a thickness of 800 μm is coated on the surface of the paste layer. This film is then hot-pressed and cured to form copper grid lines. The flexible composite film is removed. The hot-pressing curing temperature is 300℃, the hot-pressing curing pressure is 500 Pa, and the hot-pressing curing time is 1 s. Finally, a magnesium fluoride layer is prepared on the surface of the silicon wafer with the copper grid lines using a thermal evaporation method. The wafer is then subjected to light injection treatment in a low-oxygen atmosphere. The light injection temperature is 220℃, and the light injection intensity is 60 sun. A heterojunction solar cell is obtained by using a light injection time of 90s and an oxygen content of 200ppm in a low-oxygen atmosphere. The flexible composite film includes a polytetrafluoroethylene substrate and a dimethyl silicone oil curing layer covering the surface of the polytetrafluoroethylene substrate. The thickness of the dimethyl silicone oil curing layer is 5μm. The copper grid line includes a first region for solder ribbon connection and a second region other than the first region. The thickness of the magnesium fluoride layer covering the first region is 25nm, and the thickness of the magnesium fluoride layer covering the second region is 100nm.
[0097] Example 4
[0098] Example 4 differs from Example 1 only in that it does not include the step of preparing a silicon nitride layer on the surface of a silicon wafer with copper grid lines using PECVD; all other conditions are the same, resulting in a heterojunction solar cell.
[0099] Example 5
[0100] Example 5 differs from Example 1 only in that it does not include the step of placing the silicon wafer with the copper grid lines in a low-oxygen atmosphere for light injection treatment; all other conditions are the same, resulting in a heterojunction solar cell.
[0101] Example 6
[0102] Example 6 differs from Example 1 only in that it does not include the step of preparing a silicon nitride layer on the surface of a silicon wafer with copper grid lines using PECVD and then performing light injection treatment under a nitrogen atmosphere; all other conditions are the same, resulting in a heterojunction solar cell.
[0103] Example 7
[0104] Example 7 differs from Example 1 only in that the copper paste described above is screen-printed onto both sides of a silicon wafer, dried to form a paste layer, and then a dimethyl silicone oil containing benzoyl peroxide curing agent is coated onto the surface of the paste layer. After drying and hot-pressing curing, copper grid lines covered with a dimethyl silicone oil curing layer are formed. The dimethyl silicone oil containing benzoyl peroxide curing agent is formed by mixing benzoyl peroxide curing agent and dimethyl silicone oil, and the mass fraction of dimethyl silicone oil in the dimethyl silicone oil containing benzoyl peroxide curing agent is 99%. The dimethyl silicone oil containing benzoyl peroxide curing agent is coated with a paste layer. The mass fraction of the silicon wafer layer is 0.1%, the hot-press curing temperature is 275℃, the hot-press curing pressure is 1000Pa, and the hot-press curing time is 3s. A silicon nitride layer is prepared on the surface of the silicon wafer with copper grid lines using PECVD, and then light injection is performed in a low-oxygen atmosphere. All other conditions are the same to obtain a heterojunction solar cell. The copper grid lines include a first region for solder ribbon connection and a second region other than the first region. The thickness of the dimethyl silicone oil curing layer covering the first region is 2nm, and the thickness of the dimethyl silicone oil curing layer covering the second region is 105nm.
[0105] Example 8
[0106] Example 8 differs from Example 2 only in that the copper paste described above is screen-printed onto both sides of a silicon wafer, dried to form a paste layer, and then a dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent is coated onto the surface of the paste layer. After drying and hot-pressing curing, copper grid lines covered with a dimethyl silicone oil curing layer are formed. The dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent is formed by mixing methyl ethyl ketone peroxide curing agent and dimethyl silicone oil, and the mass fraction of dimethyl silicone oil in the dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent is 99.5%. The mass fraction of the dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent on the silicon wafer with the paste layer is 0.1%. The hot-pressing curing temperature is... The temperature was 200℃, the hot-pressing curing pressure was 90Pa, and the hot-pressing curing time was 30s. A silicon nitride layer was prepared on the surface of a silicon wafer with copper grid lines using PECVD, and then light injection was performed in a low-oxygen atmosphere. All other conditions were the same to obtain a heterojunction solar cell. The copper grid lines included a first region for solder ribbon connection and a second region other than the first region. The thickness of the dimethyl silicone oil curing layer covering the first region was 2nm, the thickness of the dimethyl silicone oil curing layer covering the second region was 105nm, and the thickness of the silicon nitride layer covering the first region was 2nm and the thickness of the silicon nitride layer covering the second region was 25nm.
[0107] Example 9
[0108] Example 9 differs from Example 3 only in that the copper paste described above is screen-printed onto both sides of a silicon wafer, dried to form a paste layer, and then a dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent is coated onto the surface of the paste layer. After drying and hot-pressing curing, copper grid lines covered with a dimethyl silicone oil curing layer are formed. The dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent is formed by mixing methyl ethyl ketone peroxide curing agent and dimethyl silicone oil, and the mass fraction of dimethyl silicone oil in the dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent is 99.6%. The mass fraction of the dimethyl silicone oil containing methyl ethyl ketone peroxide curing agent on the silicon wafer with the paste layer is 0.1%. Hot-pressing curing is then performed. The temperature is 300℃, the hot-press curing pressure is 500Pa, and the hot-press curing time is 1s. A magnesium fluoride layer is prepared on the surface of a silicon wafer with copper grid lines by thermal evaporation, and then light injection is performed in a low-oxygen atmosphere. All other conditions are the same to obtain a heterojunction solar cell. The copper grid lines include a first region for solder ribbon connection and a second region other than the first region. The thickness of the dimethyl silicone oil curing layer covering the first region is 2nm, the thickness of the dimethyl silicone oil curing layer covering the second region is 105nm, and the thickness of the magnesium fluoride layer covering the first region is 5nm and the thickness of the magnesium fluoride layer covering the second region is 50nm.
[0109] Example 10
[0110] Example 10 differs from Example 7 only in that it does not include the step of preparing a silicon nitride layer on the surface of a silicon wafer with copper grid lines using PECVD; all other conditions are the same, resulting in a heterojunction solar cell.
[0111] Example 11
[0112] Example 11 differs from Example 7 only in that it does not include the step of placing the silicon wafer with the copper grid lines in a low-oxygen atmosphere for light injection treatment; all other conditions are the same, resulting in a heterojunction solar cell.
[0113] Example 12
[0114] Example 12 differs from Example 7 only in that it does not include the step of preparing a silicon nitride layer on the surface of a silicon wafer with copper grid lines using PECVD and then performing light injection treatment under a nitrogen atmosphere; all other conditions are the same, resulting in a heterojunction solar cell.
[0115] Example 13
[0116] The only difference between Example 13 and Example 7 is that the thickness of the octadecyl mercaptan layer is 0.1 nm; all other conditions are the same, and a heterojunction solar cell is obtained.
[0117] Example 14
[0118] The only difference between Example 14 and Example 7 is that the thickness of the octadecyl mercaptan layer is 60 nm; all other conditions are the same, resulting in a heterojunction solar cell.
[0119] Example 15
[0120] Example 15 differs from Example 7 only in that the dimethyl silicone oil containing benzoyl peroxide curing agent also contains silver powder. In the dimethyl silicone oil containing benzoyl peroxide curing agent, the mass fraction of dimethyl silicone oil is 94.5%, the mass fraction of silver powder is 5%, and the mass fraction of benzoyl peroxide curing agent is 0.5%. All other conditions are the same, resulting in a heterojunction solar cell. In this case, the mass fraction of silver powder in the dimethyl silicone oil curing layer is 5%.
[0121] Example 16
[0122] Example 16 differs from Example 15 only in that the dimethyl silicone oil containing benzoyl peroxide curing agent also contains carbon nanotubes. In the dimethyl silicone oil containing benzoyl peroxide curing agent, the mass fraction of dimethyl silicone oil is 74.8%, the mass fraction of carbon nanotubes is 25%, and the mass fraction of benzoyl peroxide curing agent is 0.2%. All other conditions are the same, resulting in a heterojunction solar cell, wherein the mass fraction of carbon nanotubes in the dimethyl silicone oil curing layer is 25%.
[0123] Example 17
[0124] Example 17 differs from Example 15 only in that the dimethyl silicone oil containing benzoyl peroxide curing agent also contains carbon black. In the dimethyl silicone oil containing benzoyl peroxide curing agent, the mass fraction of dimethyl silicone oil is 49.9%, the mass fraction of carbon black is 50%, and the mass fraction of benzoyl peroxide curing agent is 0.1%. All other conditions are the same, resulting in a heterojunction solar cell, wherein the mass fraction of carbon black in the dimethyl silicone oil curing layer is 50%.
[0125] Comparative Example 1
[0126] The only difference between Comparative Example 1 and Example 1 is that the surface of the copper powder is not coated with an octadecyl mercaptan layer; all other conditions are the same, and a heterojunction solar cell is obtained.
[0127] Comparative Example 2
[0128] Compared with Example 1, Comparative Example 2 differs only in that copper powder with an aminotrimethylphosphonic acid layer on its surface is used instead of copper powder with an octadecyl mercaptan layer on its surface; all other conditions are the same, and a heterojunction solar cell is obtained.
[0129] Comparative Example 3
[0130] Comparative Example 3 differs from Example 1 only in that it does not include the step of covering the surface of the slurry layer with a flexible composite film with a thickness of 50 μm; all other conditions are the same, and a heterojunction solar cell is obtained.
[0131] Comparative Example 4
[0132] Comparative Example 4 differs from Example 1 only in that a polyimide film is used instead of a flexible composite film; all other conditions are the same, resulting in a heterojunction solar cell.
[0133] Comparative Example 5
[0134] Comparative Example 5 differs from Example 1 only in that copper grid lines are formed after curing, and the flexible composite film is removed. The curing temperature is 160°C and the curing time is 3 seconds. All other conditions are the same, resulting in a heterojunction solar cell.
[0135] Comparative Example 6
[0136] Compared with Example 7, Comparative Example 6 differs only in that the surface of the copper powder is not coated with an octadecyl mercaptan layer; all other conditions are the same, and a heterojunction solar cell is obtained.
[0137] Comparative Example 7
[0138] Comparative Example 7 differs from Example 7 only in that copper powder with an aminotrimethylphosphonic acid layer on its surface is used instead of copper powder with an octadecyl mercaptan layer on its surface; all other conditions are the same, and a heterojunction solar cell is obtained.
[0139] Comparative Example 8
[0140] Comparative Example 8 differs from Example 7 only in that it does not include the step of coating the surface of the slurry layer with dimethyl silicone oil containing benzoyl peroxide curing agent; all other conditions are the same, and a heterojunction solar cell is obtained.
[0141] Comparative Example 9
[0142] Compared with Example 7, Comparative Example 9 differs only in that copper grid lines are formed by curing, wherein the curing temperature is 160°C and the curing time is 3s; all other conditions are the same, resulting in a heterojunction solar cell.
[0143] The performance of the copper grid lines and heterojunction solar cells prepared in Examples 1-17 and Comparative Examples 1-9 were tested respectively. The test results are shown in Table 1. The specific test methods are as follows:
[0144] Line resistivity testing of copper grid lines: TLM method was used for testing.
[0145] Moisture barrier performance test of copper grid wire: The test is conducted according to the damp heat measurement method in the IEC 61215 series standards. The test conditions are: after maintaining the temperature at 85℃ and 85% relative humidity for 1000 hours, the attenuation rate is measured, i.e., DH1000 attenuation rate / .
[0146] Performance parameter testing of heterojunction solar cells: Testing was conducted using an IV analyzer, with a test condition of 1000 W / m. 2 25℃.
[0147] Table 1
[0148]
[0149] Based on the data in Table 1, compared to Examples 1-3 and 7-9, when the thickness of the silicone oil curing layer covering the surface of the copper grid line is greater than zero, the water vapor barrier performance and oxidation resistance of the copper grid line can be significantly improved, thus improving the efficiency of the solar cell. Compared to Examples 1 and 4-6, and Examples 7 and 10-12, preparing an oxidation-resistant layer and / or performing light injection treatment on the surface of the copper grid line can further improve the water vapor barrier performance and oxidation resistance of the copper grid line, thus improving the efficiency of the solar cell. Compared to Examples 7 and 13-14, controlling the thickness of the reducing organic layer covering the surface of the copper powder within a suitable range is beneficial to improving the oxidation resistance of the copper powder, effectively reducing the linear resistivity of the copper grid line, and improving the efficiency of the solar cell. Compared to Examples 7 and 15-17, when the thickness of the silicone oil curing layer covering the surface of the copper grid line is greater than zero, and the silicone oil curing layer contains conductive particles, it can improve the oxidation resistance of the copper powder while further reducing the linear resistivity of the copper grid line, thus improving the efficiency of the solar cell.
[0150] Compared with Examples 1 and Comparative Examples 1-5 and Examples 7 and Comparative Examples 6-9, in the solar cell preparation method of the present invention, the copper particles in the copper paste are copper powder with a reducing organic layer on the surface. Simultaneously, a flexible composite film with a specific structure or silicone oil containing a curing agent is used, along with a hot-pressing curing process. Under this synergistic effect, the copper paste can effectively inhibit the oxidation of copper particles during the entire solar cell metallization process, ensuring that the copper powder in the copper paste is almost entirely pure copper powder. This results in low porosity and high density of the final copper grid lines, significantly reducing the linear resistivity of the copper grid lines and improving the efficiency of the solar cell and photovoltaic module. At the same time, it reduces the permeation paths of water vapor and oxygen to a certain extent, providing a certain degree of water vapor barrier, which is beneficial to improving the reliability of the photovoltaic module. Moreover, when silicone oil containing a curing agent is used, the silicone oil containing the curing agent forms a silicone oil curing layer on the surface of the copper grid lines as a protective layer, which can significantly improve the oxidation resistance and water vapor barrier of the copper grid lines, effectively improving the reliability of the photovoltaic module.
[0151] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0152] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A solar cell, comprising a silicon wafer and grid lines disposed at least on the surface of the silicon wafer, characterized in that, The gate line is a copper gate line, and the surface of the copper gate line is coated with a silicone oil curing layer with a thickness of 0nm-500nm, and the line resistivity of the copper gate line is less than or equal to 8×10⁻⁶. -7 Ω·m.
2. The solar cell according to claim 1, characterized in that, The copper grid line includes a first region for solder ribbon connection and a second region other than the first region. The thickness of the silicone oil curing layer covering the first region is 0nm-100nm, and the thickness of the silicone oil curing layer covering the second region is 100nm-500nm.
3. The solar cell according to claim 1, characterized in that, The resistivity of the copper grid wire is 8 × 10⁻⁶. -7 Ω·m⁻¹×10 -8 Ω·m.
4. The solar cell according to any one of claims 1-3, characterized in that, The surface of the copper grid line is also covered with an anti-oxidation layer, and the silicone oil curing layer is located between the anti-oxidation layer and the copper grid line; And / or, the silicone oil curing layer contains conductive particles, and the mass fraction of the conductive particles in the silicone oil curing layer is 5%-50%.
5. The solar cell according to claim 4, characterized in that, The copper grid line includes a first region for solder ribbon connection and a second region other than the first region. The thickness of the antioxidant layer covering the first region is 1nm-50nm, and the thickness of the antioxidant layer covering the second region is 20nm-200nm. And / or, the material of the antioxidant layer is selected from silicon nitride and / or magnesium fluoride.
6. A method for preparing a solar cell, characterized in that, Includes the following steps: A copper paste is provided, wherein the copper particles in the copper paste are copper powder with a reducing organic layer on the surface; The copper paste is placed on at least one surface of a silicon wafer and dried to form a paste layer. A flexible composite film is then covered on the surface of the paste layer and a copper grid line is formed by hot pressing and curing. The flexible composite film is removed to obtain a solar cell. The flexible composite film includes a flexible substrate and a silicone oil curing layer covering the surface of the flexible substrate, and the hot pressing and curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer. Alternatively, a copper paste may be provided, wherein the copper particles in the copper paste are copper powder with a reducing organic layer on the surface; The copper paste is placed on at least one surface of a silicon wafer to form a paste layer. Then, silicone oil containing a curing agent is placed on the surface of the paste layer. After drying and hot pressing curing, copper grid lines are formed to obtain a solar cell. The hot pressing curing temperature is greater than or equal to the thermal decomposition temperature of the reducing organic layer.
7. The method for preparing a solar cell according to claim 6, characterized in that, The copper slurry contains 80%-90% copper particles by mass. And / or, the thickness of the reducing organic layer is 1 nm-50 nm; And / or, the material of the reducing organic layer is selected from thiols and / or isopropanol or copper formate or ethanol or a mixture of thiols and copper formate; And / or, the hot-press curing temperature is 200℃-300℃, the hot-press curing pressure is 10Pa-10KPa, and the hot-press curing time is 1s-30s; And / or, the mass fraction of the silicone oil containing the curing agent on the silicon wafer with the slurry layer is 0.01%-1%; And / or, the silicone oil containing the curing agent also contains conductive particles, wherein the mass fraction of the conductive particles in the silicone oil containing the curing agent is 5%-50%.
8. The method for preparing a solar cell according to claim 6, characterized in that, The thickness of the flexible composite film is 20μm-1000μm; And / or, the thickness of the silicone oil curing layer in the flexible composite film is 0.1 μm-10 μm; And / or, the material of the flexible substrate is selected from at least one of polyimide, polytetrafluoroethylene, and glass fiber.
9. The method for preparing a solar cell according to any one of claims 6-8, characterized in that, The method for preparing the solar cell further includes: preparing an anti-oxidation layer on the surface of a silicon wafer with the copper grid lines, and / or performing a light injection treatment on the silicon wafer with the copper grid lines under a low-oxygen atmosphere, wherein the oxygen content in the low-oxygen atmosphere is 100ppm-500ppm.
10. A photovoltaic module, characterized in that, The photovoltaic module includes the solar cell as described in any one of claims 1-5.